Two Non-indigenous Dreissenids (Dreissena polymorpha and D. rostriformis bugensis) in a Southern Baltic Coastal Lagoon: Variability in Populations of the “Old” and a “New” Immigrant - Wawrzyniak-Wydrowska, Brygida; Radziejewska, Teresa; Skrzypacz, Anna; Woźniczka, Adam (Frontiers in Marine Science, 2019)
Dreissena polymorpha and D. rostriformis bugensis are freshwater Ponto-Caspian bivalve species, at present widely distributed in Europe and North America. In the Szczecin Lagoon (a southern Baltic coastal lagoon), the quagga was recorded for the first time in 2014 and found to co-occur with the zebra mussel, a long-time resident of the Lagoon. As the two species are suspected of being competitors where they co-occur, their population dynamics was followed at a site the new immigrant was discovered (station ZS6, northern part of the Lagoon) by collecting monthly samples in 2015-2017. The abundance and biomass of the two congeners showed wide fluctuations, significant differences being recorded between months within a year and between years. The abundance and biomass proportions between the two congeners changed from an initial domination of the newcomer quagga until mid-2015 to a persistent domination of the zebra mussel throughout the remainder of the study period. Both the abundance and biomass of the two dreissenids showed a number of significant associations with environmental variables, notably with salinity, chlorophyll a content, and temperature. The co-occurrence of the two dreissenids in the Lagoon is discussed in the context of their invasion stage; it is concluded that while the quagga seems to have achieved the “outbreak” stage, the zebra mussel, an “accommodated” invader present prior to the quagga immigration, reverted to that stage.